Historical Overview of Vascular Allograft Transplantation - Kerbi Alejandro Guevara-Noriega (Radcliffe Medical Media, 2019)
There is a mix of therapeutic options for revascularisation in vascular surgery. The authors performed a literature review on the evolution of vascular allograft transplantation and its use and acceptance by vascular surgeons. This review exposed three stages: the first stage involved preliminary experimentation; the second stage was a decline in use due to long-term complications, and the third stage is its current use in special indications subject to a thorough analysis. There are few indications for the use of vascular allografts in clinical guidelines. However, there are publications of long series of case studies with variable results reflecting international use of the procedure. There is a current trend that favours its use with limited and individualised indications.